Developing a Corporate Integrity Model Through Islamic Social Reporting (ISR) in Small and Medium-Sized Enterprises (SME) in Indonesia - Setyaningsih, Nina Dwi; Wahidmurni, Wahidmurni; Wahyuni, Nanik; Waeno, Mahamadaree (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
This study proposes a corporate integrity model for Small and Medium Enterprises (SMEs) in Indonesia by applying Islamic Social Reporting (ISR). Rooted in Sharia principles—justice, transparency, and social responsibility—this model aims to enhance integrity in SMEs. The study identifies critical ISR elements suited to the SME context using a Systematic Literature Review (SLR) and bibliometric analysis. Results demonstrate that ISR can improve trustworthiness and public image, contributing to SMEs' sustainability by strengthening stakeholder relationships. Despite its benefits, ISR implementation faces challenges, including resource constraints and limited awareness among SMEs. This study recommends capacity-building and training initiatives to facilitate ISR adoption, supporting a more effective integrity model for Indonesian SMEs.